Silence - Kamps, Toby.; Menil Collection (Houston, Tex.); Berkeley Art Museum and Pacific Film Archive; Seid, Steve; Sorkin, Jenni (2012)
"Explores silence in 20th and 21st century art and films, including works by Joseph Beuys, Maya Deren, Christian Marclay, Bruce Nauman, Robert Rauschenberg, and Doris Salcedo"--
Published in conjunction with the exhibition Silence. Organized by The Menil Collection, Houston, and the University of California, Berkeley Art Museum and Pacific Film Archive.
Includes bibliographical references.
boek